Ibrahim M. Abu Rabi’ Tentang Respon Islam dan Kritik Historis - Chafid Wahyudi (Tebuireng: Journal of Islamic Studies and Society, 2021)
This article departs from Ibrahim Abu Rabi's criticism of the negative western view of Islam. Islam has been labeled by the west as radical, terrorist, anti-Western, anti-democratic and others. On the other hand, Abi Rabi' wants to show that there are complexities in Islam, one of which is because of colonialism. As a result, there were various Islamic responses to colonialism. Abu Arabi' noted that there were three responses, namely modernization, nationalism, and religious revivalism. He saw the emergence of Islamic movements as a response to colonialism in several Muslim countries that failed to create good modernization, such as education and democracy. To open up modernization, especially in Islamic education, Abu Rabi' offers a historical criticism approach by understanding inclusive theology, the dominance of texts and religion as social-anthropological facts. The combination of these various approaches becomes Abu Rabi's offer as a historical critique of Islam.